2016
DOI: 10.1002/adma.201603000
|View full text |Cite
|
Sign up to set email alerts
|

Robust Underwater Oil‐Repellent Material Inspired by Columnar Nacre

Abstract: Inspired by natural columnar nacre, artificial montmorillonite/hydroxyethyl cellulose columnar nacre-like materials with a site-specific layered structure in the interior and a hierarchical columnar structure on the surface are prepared. The materials exhibit improved tensile strength, good chemical stability in seawater, superior resistance to sand-grain impingement, and robust underwater low-adhesive superoleophobicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 38 publications
3
98
0
Order By: Relevance
“…As shown in Figure S10 (Supporting Information), the hardness and tensile strength of the NIM films are 2.48 ± 0.59 GPa and 113.07 ± 12.64 MPa as determined by the nanoindentation and tensile tests, respectively. As shown in Figure e, both the hardness and Young's modulus of the NIM films are higher than those of the reported underwater superoleophobic materials including double‐network hydrogels and organic–inorganic composite materials . Hence, the NIM films can achieve durable superoleophobicity, even after suffering harsh treatments such as sand grain impingement, which is promising for underwater oil‐repellent materials.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure S10 (Supporting Information), the hardness and tensile strength of the NIM films are 2.48 ± 0.59 GPa and 113.07 ± 12.64 MPa as determined by the nanoindentation and tensile tests, respectively. As shown in Figure e, both the hardness and Young's modulus of the NIM films are higher than those of the reported underwater superoleophobic materials including double‐network hydrogels and organic–inorganic composite materials . Hence, the NIM films can achieve durable superoleophobicity, even after suffering harsh treatments such as sand grain impingement, which is promising for underwater oil‐repellent materials.…”
mentioning
confidence: 90%
“…Underwater superoleophobic materials have shown widely promising applications in various fields to address the rapidly growing issues in marine environment, especially the highly frequent oil‐spill accidents . To achieve underwater superoleophobicity, high‐surface‐energy materials with hierarchical micro/nanostructures are required to trap water molecules on their surfaces and subsequently to form a water cushion to repel oil droplets . However, these hierarchical micro/nanostructures can render the coatings the non‐transparent because of the extensive light scattering effect, which significantly hinders their application in underwater optical equipment and devices such as swimming goggles and underwater cameras.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] This bio-inspired superhydrophobicity that extremely repels water is highly capable of providing materials (membrane, absorbent, etc.) and the lack of stability of these underwater conventionalw ettable materials,w hich are generally prepared throughp olymerich ydrogel and metaloxide coatings in diversea nd complex chemical/physical environments, [28,29] are the major drawbacks behind their widespread application towardo il-water separation in practically relevant settings.I na ddition to this, this gravity-driven and energy-efficient filtration principle,w hich demands adequate precontainment anda ctive filtration, would be useful in avoiding oil contaminations from regulari ndustrial discharge, but has limited prospect in cleaning of contaminated oil from sea and otherv ast water reservoirs. [8][9][10][11][12] However,t his antifouling property has inherentl imited stabilityi np ractically relevant settings, and the extreme water repellency gets easily compromised after submerging the material even in deionized (DI) water,o wing to the removal of am etastable thin layer of trapped air,w hich is essentially conferred to the Cassie-Baxter state.…”
mentioning
confidence: 99%
“…[14][15][16] As an alternative, another types of special hierarchicali nterfaces that extremely repel oil under water (superoleophobicity,o il droplets are extremelyr epelled by the interface with advancingo il-contact angle above 1508) [17] were introduced in the literaturei nr ecent past for removing the aqueous phase from oil-water mixtures. and the lack of stability of these underwater conventionalw ettable materials,w hich are generally prepared throughp olymerich ydrogel and metaloxide coatings in diversea nd complex chemical/physical environments, [28,29] are the major drawbacks behind their widespread application towardo il-water separation in practically relevant settings.I na ddition to this, this gravity-driven and energy-efficient filtration principle,w hich demands adequate precontainment anda ctive filtration, would be useful in avoiding oil contaminations from regulari ndustrial discharge, but has limited prospect in cleaning of contaminated oil from sea and otherv ast water reservoirs. and switchable smart interfaces werea lso designed and all such interfaces were exclusively exploited in filtration-based oil-waters eparation using both modifiedm embranesa nd mesh.…”
mentioning
confidence: 99%
“…3,6,[19][20][21] There are plenty of hierarchical micro/nanostructure surfaces which have been inspired by nature. [22][23][24][25][26] Jiang et al reviewed the designs of bioinspired multifunctional materials 27 and indicated that biological surfaces have some unique properties e.g. wettability, mechanical properties, structure color, and optical properties.…”
Section: Introductionmentioning
confidence: 99%